'I'm not a real boozer': a qualitative study of primary care patients' views on drinking and its consequences. (18th April 2018) - Khadjesari, Z; Stevenson, F; Toner, P; Linke, S; Milward, J; Murray, E
Abstract: Background: The public health message around alcohol is complex, with benefits versus harms, the confusing concept of risk and drinking guidance changing over time. This provides a difficult context for alcohol screening in primary care, with established barriers from the practitioner perspective, but less is known about the patients' perspective. This study explores patients' views on drinking. Methods: Eligible participants were recorded as drinking above low risk levels in primary care. Six practices in North London participated. Interviews were in-depth, semi-structured, transcribed verbatim and underwent detailed thematic analysis. Findings: Interviews were conducted with 8 women and 12 men, aged 26–83 years, mostly educated to undergraduate level and of 'White' ethnicity. UK drinking guidance was viewed as irrelevant for reasons related to life stage, lifestyle and absence of harm. Dependence, loss of functionality and control were perceived as key features of problematic drinking. Healthy lifestyles, in terms of diet, exercise and not smoking, were thought to mitigate potential problems associated with alcohol intake. Conclusion: The findings suggest that public health messages and brief advice should focus on harm experienced at different life stages, among people with different lifestyles, to challenge the ubiquitous view that 'I'm not a real boozer'.